Electrochemical determination of flubendiamide insecticide at graphite/ionic liquid/natural phosphate: Application in water and white rice - S. Aghris; N. Ajermoun; A. Hrioua; F. Laghrib; Y. El Bouabi; S. Saqrane; A. Farahi; M. Bakasse; S. Lahrich; M.A. El Mhammedi (Case Studies in Chemical and Environmental Engineering, 2022)
In this work, a pencil graphite electrode modified with ionic liquid and natural phosphate (PGE/IL/NPht) was manufactured for the insecticide flubendiamide (FBD) sensing in water and white rice. The reduction current of the FBD was linearly dependent on the concentration over the linear range of 9.0 × 10−7–5.0 × 10−5 mol L−1 (R2 = 0.997) with a limit of detection of 2.0 × 10−8 mol L−1. Possible interferences of several inorganic species such as Cu2+, Mg2+, and Na+ and pesticides such as thiamethoxam, imidacloprid, and 4-nitrophenol were also carried out. The results show that their existence has no effect on the analysis of FBD and its reduction potential is not affected. Moreover, the established sensor proved to be a viable alternative to the conventional methods for FBD detection in water and white rice even without sample cleanup.